Prime evil: In his own words: De Kock, E & Gordin, J (1988) A long night’s damage: Working for the Apartheid State. Johannesburg: Contra Press. ISBN 0-620-22198-4 pbk. 331 pages - Earl-Taylor, Mike (PINS-Psychology in Society, 2026)
From a socio-historical perspective, A long night’s damage: Working for the Apartheid State provides the reader with an invaluable insight into the mind-set and the amorality of the South African State during the so-called "Total Onslaught", through the experiences of former South African Police Colonel, Eugene De Kock. The book documents the grim exploits of De Kock, at one time the Apartheid government’s most efficient political assassin, when shooting, burning, poisoning and blowing up bodies of anti-Apartheid activists was the "patriotic" norm for certain sections of the Security Branch Police. Now 51 years old, De Kock is serving a double-life sentence, plus 212 years, in Pretoria Central Maximum Security Prison, for 89 crimes, including 6 murders.